2018
DOI: 10.1186/s40780-018-0123-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coadministration of rifampicin on the pharmacokinetics of linezolid: clinical and animal studies

Abstract: BackgroundCombination therapy of linezolid (LZD) and rifampicin (RFP) may be more effective than monotherapy for treating gram-positive bacterial infections, but several studies have suggested that RFP decreases LZD exposures, thereby increasing the risk of therapeutic failure and emergence of LZD-resistant strains. However, the mechanism of the drug-drug interaction between LZD and RFP is unknown.MethodsWe conducted a prospective, open-label, uncontrolled clinical study in Japanese patients receiving LZD and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 35 publications
0
8
1
Order By: Relevance
“…Linezolid is an oxazolidinone protein synthesis inhibitor that is sometimes combined with the transcriptional inhibitor, rifampicin, for the treatment of S. aureus infections 29,30 . Linezolid/rifampicin reduced viable cells within the biofilm by almost 3-logs but was not significantly potentiated by US-PCCA.…”
Section: Resultsmentioning
confidence: 99%
“…Linezolid is an oxazolidinone protein synthesis inhibitor that is sometimes combined with the transcriptional inhibitor, rifampicin, for the treatment of S. aureus infections 29,30 . Linezolid/rifampicin reduced viable cells within the biofilm by almost 3-logs but was not significantly potentiated by US-PCCA.…”
Section: Resultsmentioning
confidence: 99%
“…Hashimoto et al demonstrated in animal studies that although the AUC, Cmax, and bioavailability of oral linezolid were reduced by rifampicin by 48%, 54%, and 48%, respectively, no impact was detected on the intravenously administered drug, although this difference was not attributed to altered intestinal permeability. 54 Similarly, animal studies by Okazaki et al 55 reported that the combination of linezolid with rifampicin inhibited its absorption and promoted its elimination, but not via the microsomal enzyme system. They rather suggested that the combination of linezolid and rifampicin reduced linezolid blood concentrations through metabolic enzyme pathways.…”
Section: Use In the Elderlymentioning
confidence: 97%
“…Consistent evidence is now available showing that concomitant administration of rifampicin can significantly reduce the systemic exposure of linezolid, with effect that may persist for up to 2 weeks after rifampicin discontinuation [ 60 , 61 , 62 ]. In vitro studies documented that rifampicin-inducible drug-metabolizing enzymes have a very minor contribution to linezolid clearance.…”
Section: Antibiotics As Victims or Perpetrators Of Pddismentioning
confidence: 99%
“…In vitro studies documented that rifampicin-inducible drug-metabolizing enzymes have a very minor contribution to linezolid clearance. A large increase in expression of an enzyme (e.g., CYP3A4) that normally plays a relatively modest role in linezolid elimination and/or rifampicin-induced high expression of transport proteins (i.e., p-glycoprotein) have been hypothesized as causes for the observed reduction of linezolid concentrations [ 60 , 61 , 62 ].…”
Section: Antibiotics As Victims or Perpetrators Of Pddismentioning
confidence: 99%